SINGLE NUCLEOTIDE POLYMORPHISM (SNP) IDENTIFICATION of CIRCUMSPOROZOITE PROTEIN GENE in Plasmodium falciparum FROM MALARIA PATIENTS IN WORKING AREA of PRIMARY HEALTH CARE HANURA, PESAWARAN, LAMPUNG - Diah Balqis Ikfi Hidayati (Yayasan Pendidikan Medika Indonesia, 2022)
Malaria is an infectius disease caused by Plasmodium sp. The treatment for malaria with Artemisinin-based Combination Therapy (ACT) can cause resistance, so a new effort is needed to reduce the morbidity of malaria. A better prevention method for preventing malaria is to use vaccine. The RTS,S/AS01 vaccine is the first generation malaria vaccine that has been applied in Ghana, Kenya and Malawi since early 2018. The vaccine consists of circumsporozoite protein (CSP) antigen. This study aims to detect the presence of SNPs in CSP that are useful as a database of genetic variation for vaccine development in Indonesia.This type of research is a descriptive research with survey design. The sample of research was obtained from Biological Saved Materials (BSM) as many as 53 samples. The examination was performed using by PCR method and followed by a sequencing process to detect SNP. The results showed that only 16 samples had high DNA concentration and the sequencing results showed there is no difference in nucleotide base sequences compared to references on Pf3D7 isolates from Gene Bank. So the conclusion is there is no SNP on the CSP gene in Plasmodium falciparum from malaria patients in the working area of Primary Health Care Hanura, Pesawaran, Lampung.